(untitled) (Journal of Contemporary Philology, 2021)
The aim of this paper is comparative analysis of two wartime novels: Men or Not Men by Elio Vittorini and A private matter by Beppe Fenoglio, based on the love theme. The comparative analysis showed that there are few points that are common for both novels: the autobiographical elements, and the common inspiration model – Hemingway’s novel For Whom the Bell Tolls. The “absence” of the female protagonists is notable in both novels, namely they are superficially represented or are present only in the memories. However, we asserted that they are very important figures in the novels: they are symbols of hope and of life itself. The analysis also revealed another common characteristic: what persists in regard to the male protagonists is the impossibility that they would find their path to a future life. Their love defeat deprives them of the necessary hope and both protagonists commit “suicide” with the help of the enemy. Thus, we concluded that the love motive is neither secondary nor does it have a mere “decorative” function in this novels, but is rather interwoven in their structure as an impetus of the protagonists’ action or as a motive for their death.